Awareness of and participation in mass drug administration programs used for onchocerciasis control in the Atwima Nwabiagya North District, Ghana - Francis Adjei Osei; Sam Kofi Tekyi Newton; Isaac Nyanor; Eugene Osei-Yeboah; Evans Xorse Amuzu; Nicholas Karikari Mensah; Obed Ofori Nyarko; Ernest Amanor; Samuel Frimpong Odoom; Suraj Yawnumah Abubakar; Mathias Dongyele; Aliyu Mohammed; et al. (BMC, 2023)
Abstract Background Studies on Mass drug administration (MDA) in Ghana targeting various diseases, have mostly focused on factors that affect coverage and compliance to MDA with limited focus on evidence regarding awareness and community perception of the program. Therefore, this study sought to provide empirical evidence on the knowledge of onchocerciasis, and awareness of and participation in the MDA among community members. Methods A community-based cross-sectional survey was conducted from August to October 2019 in communities within the Atwima Nwabiagya North District, Ghana. Data was collected from 2,008 respondents. Bivariate and multivariate logistic regression analyses were performed to measure the associations between socio-demographics, having heard of onchocerciasis and its prevention, and levels of awareness of the MDA program. Results A total of 1268 respondents (63.2%) were aware of the MDA program. The majority ofMost respondents (74.4%) were of the view that the information given about the program was not enough and 45.4% of the respondents had no idea about the relevance of the MDA program. Respondents who had ever heard about onchocerciasis prevention and persons who had previously participated in the MDA program were more likely to be aware of the MDA program during implementation (AOR = 2.32; 95% CI 1.79-3.01 and AOR = 9.31; 95% CI 7.06-12.26, respectively). Conclusions We observed a significant association between being aware of MDA campaigns and knowledge of onchocerciasis and its preventive methods, and participation in previous MDA campaigns. We recommend intensification and improvement of prevention campaigns regarding the onchocerciasis MDA program as key to ensuring increased MDA program participation.